Self-Regulated Learning-Based Approaches in Teacher Mentoring and Professional Development: A Systematic Review - Risdiyanto; Hernawan A. H.; Johan R. C.; Fadlillah A. F. (Jurnal Penelitian Pendidikan IPA, 2026)
The growing complexity of 21st-century education demands that teachers function not only as subject specialists but as self-regulated learners capable of sustaining their own professional growth. Despite an expanding body of research on self-regulated learning (SRL) in educational contexts, systematic reviews synthesizing SRL-based approaches in teacher professional development (TPD), particularly in relation to mentoring and advisory roles, remain limited. This study examined how SRL is integrated within TPD and its role in supporting changes in instructional practice. A systematic literature review following PRISMA 2020 guidelines was conducted, drawing on records from Scopus, ERIC, and ScienceDirect published between 2015 and 2025. Of 518 identified records, 27 articles met the inclusion criteria and were analyzed thematically. Three principal findings emerged: teachers’ SRL functions as a foundational mechanism for professional development; SRL capacity is enacted through instructional practices including explicit strategy instruction, cognitive modeling, reflective task design, and formative assessment; and the sustainability of these practices depends on relational and organizational supports such as coaching, professional learning communities, and educational technology. These findings offer a coherent framework for designing TPD programs that are reflective, adaptive, and oriented toward lifelong professional learning.